Core-shell engineered boron nitride nanotubes for enhancing dielectric properties of epoxy composites - Jun-Wen Ren; Hua-Chao Wei; Shuai Yang; Zhi-Jie Chen; Hao-Wen Yuan; Yue Zhang; Xiao-Jun Wang; Jun-Wei Zha; Shen-Li Jia (Materials & Design)
Boron nitride nanotubes (BNNTs), renowned for their exceptional properties, have emerged as innovative nanofillers for composite dielectrics. However, their practical implementation is hindered by intrinsically weak interfacial adhesion with polymer matrices. To address this limitation, herein, a core–shell nanocable architecture was designed, featuring BNNTs as the core and polydopamine as the shell, for facilitating robust interfacial interaction with the epoxy matrix from the perspective of interfacial modulation. Incorporating just 3 wt% of these nanocables introduces a multitude of deep traps within the epoxy composite dielectrics, effectively suppressing charge carrier mobility through localized electron confinement. This strategic enhancement endows the composite dielectrics with an exceptional dielectric breakdown strength of 46.36 kV/mm (a 79% increase relative to pure epoxy) and a low dielectric loss of less than 0.03 (10-1 Hz), underscoring their superior electrical insulation capabilities. In addition, the introduction of nanocables enables the composite dielectrics to achieve a synergistic enhancement in toughness to 4.17 MJ/m3 and thermal conductivity to 0.33 W/mK, surpassing the attributes of pure epoxy by 208.9% and 58.6%, respectively. These findings offer critical insights into the strategic design of multifunctional and high-performance epoxy composite dielectrics.